Effects of supplemental methionine and lysine on nutritional value of housefly larvae meal (musca domestica) fed to rats (2001)
The performance and blood composition of rats fed housefly larvae meal supplemented with, or without, methionine and lysine, or fed at high concentration were investigated. Rats fed supplemental methionine alone achieved highest body weight gain (P < 0.05). dietary supplemented of both methionine and lysine or high dietary concentration of larvae meal depressed (P < 0.05) rat feed intake. The blood composition of rats was superior (P < 0.05) on methionine-supplemented larvae meal. Additional amino acids from larvae elicited higher (P < 0.05) serum proteins, cholesterol and triglyceride; however, other blood biochemical profiles were lower (P < 0.05) than in the unsupplemented group. In conclusion, housefly larvae meal seemed deficient in methionine and it benefited the rat tremendously to supplement with this amino acid; however, additional lysine and high dietary inclusion of larvae meal as sole protein source appeared nutritionally inconsequential.